Purchasing behaviour of phone users tend to buy smartphone / Mohammad Syazwan Mohammad Rodhi - Mohammad Rodhi, Mohammad Syazwan (Faculty of Business and Management, 2019)
Smartphone is synonym in our life, people tend to use smartphone because it can easier our daily task, since the smartphone have extra features like camera. The purpose of this study is to examine the relationship between product features, brand name, product price, convenience and social influence of purchasing behaviour of smartphone among phone users. The questionnaire will be distributed to 150 of phone users who have experience using and having smartphone generally to get the random sampling method. The issue of this study to have a clear visual of why people tend to buy smartphone based on dependent variable and independent variable of the study and understanding the demand of the smartphone nowadays. In 2017 statistics shows that the number of phone users in Malaysia have reached to 19.9 million users it shows that the number people use smartphone is high and will increase in the future because of the changing in the technology.